2016
DOI: 10.1175/jas-d-15-0186.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Sensitivity of Tropical Cyclone Size and Structure to the Atmospheric Temperature Profile

Abstract: This study uses the WRF ARW to investigate how different atmospheric temperature environments impact the size and structure development of a simulated tropical cyclone (TC). In each simulation, the entire vertical virtual temperature profile is either warmed or cooled in 18C increments from an initial specified state while the initial relative humidity profile and sea surface temperature are held constant. This alters the initial amount of convective available potential energy (CAPE), specific humidity, and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…TC MPI and intensification is closely associated with the ambient temperature and moisture profile (Bister & Emanuel, ; Emanuel, ; Ge et al, ; Gilford et al, ; Stovern & Ritchie, ; Wang, Camargo, Sobel, & Polvani, ). As shown in Figure , the greatest MPI occurs in September, indicating that the evolution of MPI is different from the monthly variations of the RI ratio.…”
Section: Controlling Factorsmentioning
confidence: 99%
“…TC MPI and intensification is closely associated with the ambient temperature and moisture profile (Bister & Emanuel, ; Emanuel, ; Ge et al, ; Gilford et al, ; Stovern & Ritchie, ; Wang, Camargo, Sobel, & Polvani, ). As shown in Figure , the greatest MPI occurs in September, indicating that the evolution of MPI is different from the monthly variations of the RI ratio.…”
Section: Controlling Factorsmentioning
confidence: 99%
“…Particularly in the western North Pacific, rapidly intensifying TCs occur when environmental instability is high. Stovern and Ritchie [11] investigated the sensitivity of the TC structure to the temperature conditions and found that a warmer environment with a higher CAPE is important for the rapid development of a more intense inner-core precipitation and wind, whereas a colder environment with a lower CAPE leads to a broader inner and outer core of convection. However, in their study [11], although the temperature in the entire atmosphere was uniformly warmed or cooled by a 1 • C increment, the temperature lapse rate was unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Stovern and Ritchie [11] investigated the sensitivity of the TC structure to the temperature conditions and found that a warmer environment with a higher CAPE is important for the rapid development of a more intense inner-core precipitation and wind, whereas a colder environment with a lower CAPE leads to a broader inner and outer core of convection. However, in their study [11], although the temperature in the entire atmosphere was uniformly warmed or cooled by a 1 • C increment, the temperature lapse rate was unchanged. Some studies focused on how the temperature profile in the upper troposphere and lower stratosphere affects the intensity and structure of TCs [12][13][14], but these studies did not change the temperature in the entire troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid development and expansion of the outer rainband in OCEAN, the boundary layer inflow into the inner core was blocked, resulting in a slower intensification in the TC inner core in OCEAN. A more detailed dynamical explanation can be found in the idealized simulations in Wang (2009) and Stovern and Ritchie (2016). Once the eyewall became well organized in OCEAN after 0000 UTC 23 January, there was a more rapid increase in OCEAN intensity than in TER.…”
Section: Validation Of the Control Simulationmentioning
confidence: 94%